2019
DOI: 10.1016/j.radcr.2019.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Femoral-facial syndrome: Report of 2 fetal cases

Abstract: Femoral-facial syndrome (FFS) is a congenital disorder, characterized by facial dysmorphism and femoral hypoplasia. We describe the prenatal ultrasound and autopsy findings of FFS in 2 female fetuses born to diabetic mothers. Prenatal ultrasound showed micrognathia, low-set dysplastic ears and very short femora. Autopsy also demonstrated cleft palate, hypoplastic genitalia and visceral malformations including interventricular communication and posthemorrhagic hydrocephalus. Histologic study showed hyperplasia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…Johnson et al [5] expand the diagnostic criteria so that, for a diagnosis of FFS to be made, femoral hypoplasia along with two out of the four facial features must be present: long philtrum with thin lip, mandible/mouth hypoplasia, upslanting palpebral fissures, or undeveloped nasal alae. When describing the femoral hypoplasia, Darouich et al describe that it had been reported as symmetric in females, as in our case, but asymmetric in males [2]. Majority of the documented cases report cleft palate, abnormal vertebral size, short limbs, micrognathia and retrognathia, and micromelia (especially concerning the femur) [5,14].…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Johnson et al [5] expand the diagnostic criteria so that, for a diagnosis of FFS to be made, femoral hypoplasia along with two out of the four facial features must be present: long philtrum with thin lip, mandible/mouth hypoplasia, upslanting palpebral fissures, or undeveloped nasal alae. When describing the femoral hypoplasia, Darouich et al describe that it had been reported as symmetric in females, as in our case, but asymmetric in males [2]. Majority of the documented cases report cleft palate, abnormal vertebral size, short limbs, micrognathia and retrognathia, and micromelia (especially concerning the femur) [5,14].…”
Section: Discussionsupporting
confidence: 50%
“…Clinical manifestations reported as somewhat frequent are talipes equinovarus, xoa vara, abnormal fibular morphogenesis with hypoplasia or aplasia, hip dysplasia of the iliac or ischial bones, enlarged obturator foramen, low set ears with microtia and anotia, thin lips and elongated philtrum, upslanted fissures of the eyes, and fused sacrum and coccyx [5,14,15]. The literature also reports very rare findings such as rib fusion, sprengel anomaly, preaxial polydactyly, radioulnar synostosis, or scoliosis [2,5,14], with the latter three present in our case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These criteria are essential to help differentiate FFS from other similarly presenting conditions such as caudal dysplasia syndrome [ 1 , 2 , 6 - 8 ]. Literature on FFS is limited with approximately 70 reported cases worldwide, affecting African American, Arab, Caucasian, and Chinese populations as of 2021 [ 1 , 3 , 4 , 6 , 9 ]. Research has focused on orthopedic management and detection of FFS in utero and cases have mainly been documented in neonates, infants, and, rarely, toddlers [ 3 - 7 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%